PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAKUL KARIMAH SISWA DI MADRASAH ALIYAH BABUL FUTUH PANDAN - Ais Lima’atud Diana Cahyani; Abdul Jalil; Dwi Fitri Wiyono (VICRATINA, 2021)
In The essence of education is very important for human life, the existence of an education also greatly affects the development and survival of humans. Therefore, education is teaching and training regarding the process of one's behavior. Especially Islamic religious education teachers are not only obliged to transfer or teach students about aqidah and shari'ah but Islamic religious education teachers are required to be professional in behavior, attitudes, and always take care of themselves in things that are not good in order to change the attitudes or behavior of participants. educated in accordance with Islamic teachings that have been determined. This research is a field research, namely research that goes into the field to conduct observations, interviews, and documentation. This study uses a qualitative method. The results of this study formulate that how is the role of Islamic religious education teachers in shaping students' morality at Madrasah Aliyah Babul Futuh Pandaan and what are the supporting and inhibiting factors of Islamic religious education teachers in shaping students' morality